KEGIATAN PRAMUKA DALAM MEMBENTUK JIWA KEPEMIMPINAN SANTRI DI PONDOK PESANTREN MAJLIS TAFSIR AL-QUR’AN (MTA) MOJOGEDANG KARANGANYAR - Abdullah, Mu’in; Sukemi, Rochmawati Sholikhah; Raditya, Kahfi Rafi Hanif (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This research examines the role of Scout activities in developing leadership qualities among students at MTA Mojogedang Karanganyar Islamic Boarding School. The study focuses on the integration process of scouting values with the pesantren education system and its impact on students' leadership character formation. The research employs qualitative methods with an ethnographic approach, involving three months of participatory observation, in-depth interviews with 30 key informants, and program documentation analysis. The results show that Scout activities effectively develop students' leadership qualities through three main aspects: (1) development of basic leadership character, (2) enhancement of managerial skills, and (3) strengthening of spiritual values. The integration of scouting values with the pesantren system creates a unique and comprehensive leadership development model. The research finds that students who actively participate in Scout activities show significant improvements in self-confidence, decision-making abilities, and organizational skills. This leadership development model through Scouting in pesantren can serve as a reference for developing similar programs in other Islamic educational institutions.